WHAT IS SHARE PRICES CAN AFFECT RETURN ON ASSETS, TOTAL ASSET TURNOVER, AND CURRENT RATIO WITH FINANCIAL DISTRESS AND EARNINGS PER SHARE AS A MODERATING VARIABLE - Deni Sunaryo (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the effect of Return On Assets, Total Asset Turnover, and Current Ratio on Stock Prices with Financial Distress and Earning Per Share as moderating variables. This study uses the object of banking sub-sector companies on the Southeast Asian Stock Exchange for 2012-2020. The sampling method used in this study using a purposive sampling technique obtained 11 companies that presented complete financial statements so that a total of 25 samples were obtained. The analytical approach is descriptive statistical analysis, classical assumption test, MRA, multiple linear regression, t-test, and f test. The study's results partially concluded that Return On Assets had a significant effect on stock prices, Total Asset Turnover had no significant impact on stock prices, and the Current Ratio had a substantial effect on stock prices. However, the study's results show that Return On Assets, Total Asset Turnover, and Current Ratio significantly impact stock prices. In addition, the results of the MRA research show that Financial Distress does not moderate Return On Assets to Stock Prices, Financial Distress does not average Total Asset Turnover to Stock Prices, Financial Distress does not average Current Ratio to Stock Prices, Earning Per Share moderates Return On Assets to Stock Prices, Earning Per Share Share does not moderate Total Asset Turnover to Share Price, Earning Per Share does not reasonable Current Ratio to Share Price